Sedimentology and chronology of the advance and retreat of the last British-Irish Ice Sheet on the continental shelf west of Ireland. (15th May 2016) - Peters, Jared L.; Benetti, Sara; Dunlop, Paul; Ó Cofaigh, Colm; Moreton, Steven G.; Wheeler, Andrew J.; Clark, Christopher D.
Abstract: The last British-Irish Ice Sheet (BIIS) had extensive marine-terminating margins and was drained by multiple large ice streams and is thus a useful analogue for marine-based areas of modern ice sheets. However, despite recent advances from investigating the offshore record of the BIIS, the dynamic history of its marine margins, which would have been sensitive to external forcing(s), remain inadequately understood. This study is the first reconstruction of the retreat dynamics and chronology of the western, marine-terminating, margin of the last (Late Midlandian) BIIS. Analyses of shelf geomorphology and core sedimentology and chronology enable a reconstruction of the Late Midlandian history of the BIIS west of Ireland, from initial advance to final retreat onshore. Five AMS radiocarbon dates from marine cores constrain the timing of retreat and associated readvances during deglaciation. The BIIS advanced without streaming or surging, depositing a bed of highly consolidated subglacial traction till, and reached to within ∼20 km of the shelf break by ∼24, 000 Cal BP. Ice margin retreat was likely preceded by thinning, grounding zone retreat and ice shelf formation on the outer shelf by ∼22, 000 Cal BP. This ice shelf persisted for ≤2500 years, while retreating at a minimum rate of ∼24 m/yr and buttressing a >150-km long, 20-km wide, bathymetrically-controlled grounding zone. A large (∼150 km long), arcuate, flat-topped grounding-zone wedge, termed here the Galway Lobe Grounding-Zone Wedge (GLGZW), was deposited below this ice shelf and records a significant stillstand in BIIS retreat. Geomorphic relationships indicate that the BIIS experienced continued thinning during its retreat across the shelf, which led to increased topographic influence on its flow dynamics following ice shelf break up and grounding zone retreat past the GLGZW. At this stage of retreat the western BIIS was comprised of several discrete, asynchronous lobes that underwent several readvances. Sedimentary evidence of dilatant till deposition suggests that the readvances may have been rapid and possibly associated with ice streaming or surging. The largest lobe extended offshore from Galway Bay and deposited the Galway Lobe Readvance Moraine by <18, 500 Cal BP. Further to the north, an ice lobe readvanced at least 50 km offshore from Killary Harbour, possibly by ≤15, 100 Cal BP. The existing chronology currently does not allow us to determine conclusively whether these readvances were a glaciodynamic (internally-driven) response of the ice sheet during deglaciation or were climatically-driven. Following the <18, 500 Cal BP readvance, the Galway Lobe experienced accelerated eastward retreat at an estimated rate of ∼113 m/yr. Highlights: Our findings characterise BIIS behaviour during retreat. New radiocarbon ages constrain retreat rates. Multiple lines of evidence identify a mid-shelf stillstand. Geomorphology identifies retreat phase thinning and reconfiguration. Ice shelf buttressing slowed initial grounding zone retreat.